Crossover of Work–Life Balance Perceptions: Does Authentic Leadership Matter? - Braun, Susanne (Journal of business ethics, 2018)
This research contributes to an improved understanding of authentic leadership at the work–life interface. We build on conservation of resources theory to develop a leader–follower crossover model of the impact of authentic leadership on followers’ job satisfaction through leaders’ and followers’ work–life balance. The model integrates authentic leadership and crossover literatures to suggest that followers perceive authentic leaders to better balance their professional and private lives, which in turn enables followers to achieve a positive work–life balance, and ultimately makes them more satisfied in their jobs. Data from working adults collected in a correlational field study (N = 121) and an experimental study (N = 154) generally supported indirect effects linking authentic leadership to job satisfaction through work–life balance perceptions. However, both studies highlighted the relevance of followers’ own work–life balance as a mediator more so than the sequence of leaders’ and followers’ work–life balance. We discuss theoretical implications of these findings from a conservation of resources perspective, and emphasize how authentic leadership represents an organizational resource at the work–life interface. We also suggest practical implications of developing authentic leadership in organizations to promote employees’ well-being as well as avenues for future research.